Enteroaggregative Escherichia coli subclinical and clinical infections. Issue 5 (October 2018) - Lima, Aldo A.M.; Medeiros, Pedro H.Q.S.; Havt, Alexandre
Abstract : Purpose of review: The current review is to update the results on epidemiology, pathobiology, and genes related to virulence, clinical presentation, molecular diagnosis, antimicrobial resistance, and extraintestinal infection of enteroaggregative Escherichia coli (EAEC). Recent findings: EAEC subclinical infection was significantly associated with reduced length at 2 years of age and EAEC and coinfections were associated with reduced delta weight-for-length and weight-for-age z -scores in the first 6 months of age in the MAL-ED birth cohort study. EAEC was associated with malnutrition in children 6–24 months of age in prospective case–control studies in Bangladesh and Brazil. Virulence gene-based studies have suggested aggregative fimbriae II may be a major contributor to disease, whereas AggR-activated regulator a marker of less severe disease. The high ability of EAEC colonization likely exacerbates effects of other microbial virulence strategies. Molecular diagnosis has been useful for understanding EAEC burden, although different criteria may relate to different pathogenic outcomes. Summary: EAEC gained special interest in the past few years, especially due to association with growth decrements in children with subclinical infections and its important role as a copathogen. Understanding of EAEC pathogenesis advanced but further research is needed for elucidating both microbial and host factors influencing infection outcomes.